Philosophy and real politics - Geuss, Raymond (Princeton University Press, 2008)
Many contemporary political thinkers are gripped by the belief that their task is to develop an ideal theory of rights or justice for guiding and judging political actions. This text argues that philosophers should first try to understand why real political actors behave as they actually do.